A comparative performance analysis of a controlled d.c. and a.c. motor which emulates wind turbines for teaching and research purposes. Issue 2 (1st April 2014) - Reis, Alex; da Costa, Fernanda Hein; Xavier, Guilherme Leal; Alvarenga, Elias Barbosa; de Oliveira, José Carlos; Guimarães, Geraldo Caixeta
Abstract The growth of wind farms has motivated the development of computational and experimental approaches which supplement needs related to teaching and research in the field of engineering. Even though there have already been recognized advances made in the field of computational modeling, the development of viable means through experiment to clarify the operation of wind farm complexes has become relevant to this area. In light of these facts, this study focuses on a comparative evaluation of two strategies which emulate wind turbines: one based on d.c. motors, the other on three-phase induction motors. In both cases, the apparatus is modeled on time-domain representation techniques and motor driving structures are proposed, allowing for the reproduction of features typically found in wind turbines. Lastly, experiments are realized and the results discussed for the confirmation of potentialities, along with the efficiency of the strategies used.